PERAN ORGANISASI MASYARAKAT SEGAK SINGKAWANG DALAM MENGIMPLEMENTASIKAN NILAI GOTONG ROYONG DI SUNGAI GARAM - Yanti, Meri; Purnama, Shilmy (Universitas Tanjungpura, 2023)
This study aims to determine the implementation of the programs of the Segak Singkawang community organization in the community and to find out the description of the values of mutual cooperation by the Segak Singkawang Community Organization in Sungai Garam Village and to find out the obstacles faced by the Segak Singkawang Community Organization in implementing the values of mutual cooperation in Sungai Garam Village and to find out an overview of the values of mutual cooperation by the Segak Singkawang Community Organization in Sungai Garam Village. This research method is to use descriptive with a form of qualitative research. Data collection techniques use observation, interviews and documentation. The data subjects in this study are the Chairman, Members of the Segak Singkawang Community Organization, Chairman of the Rt and Society. Data analysis techniques use data reduction analysis, data presentation and drawing conclusions. The results of the research show that the implementation of the program there is a Segak Singkawang Community Organization program which is carried out annually, monthly and is carried out according to the situation and conditions as well as programs implemented in collaboration with the community in Sungai Garam Village.